Harnessing synthetic biology for sustainable biomining with Fe/S-oxidizing microbes - Chen, Jinjin; Liu, Yilan; Diep, Patrick; Mahadevan, Radhakrishnan (Frontiers in Bioengineering and Biotechnology, 2022)
Biomining is a biotechnological approach where microorganisms are used to recover metals from ores and waste materials. While biomining applications are motivated by critical issues related to the climate crisis (e.g., habitat destruction due to mine effluent pollution, metal supply chains, increasing demands for cleantech-critical metals), its drawbacks hinder its widespread commercial applications: lengthy processing times, low recovery, and metal selectivity. Advances in synthetic biology provide an opportunity to engineer iron/sulfur-oxidizing microbes to address these limitations. In this forum, we review recent progress in synthetic biology-enhanced biomining with iron/sulfur-oxidizing microbes and delineate future research avenues.